2022
DOI: 10.1039/d2cp02131e
|View full text |Cite
|
Sign up to set email alerts
|

A powder XRD, solid state NMR and calorimetric study of the phase evolution in mechanochemically synthesized dual cation (Csx(CH3NH3)1−x)PbX3 lead halide perovskite systems

Abstract: Mechanochemically synthesized dual cation hybrid perovskites of the form (CsxMA1−x)Pb(Cl/Br)3 (x = 0–1) exhibit complete miscibility and high structural order across each compositional range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
3
3
0
Order By: Relevance
“…The XRD spectra confirmed the successful synthesis of single crystals, indicating the coexistence of both cubic and orthorhombic phases, similar to the previous results shown in Ref. [ 37 ]. The length scale of the inhomogeneity caused by phase coexistence was estimated to be less than a few micrometers, as confirmed using micro-Raman and micro-Brillouin techniques.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The XRD spectra confirmed the successful synthesis of single crystals, indicating the coexistence of both cubic and orthorhombic phases, similar to the previous results shown in Ref. [ 37 ]. The length scale of the inhomogeneity caused by phase coexistence was estimated to be less than a few micrometers, as confirmed using micro-Raman and micro-Brillouin techniques.…”
Section: Discussionsupporting
confidence: 89%
“…The observed increase in C 11 and C 44 with increasing Cs content from 0 to 30% (from x = 1.0 to x = 0.7) suggests that the former effect was dominant. The elastic constants of pure CsPbCl 3 cannot be compared to those of the mixed crystals because they have been measured at the high temperature of 323 K. This variation in elastic constants is consistent with previous findings on the transition temperature of Cs x MA 1−x PbCl 3 [37], which decrease with higher Cs content. This indicates that a more rigid Cs x MA 1−x PbCl 3 structure tends to transform at lower temperatures.…”
Section: Elastic Properties Probed Using Brillouin Spectroscopysupporting
confidence: 85%
See 1 more Smart Citation
“…The existence of these species is corroborated by the good agreement with the GIPAW DFT calculated chemical shifts in Table 1 and Table S1, SI that are derived from the materials modelling of the MAPI defect structures and from model compounds. MAPI systems produced via spin coating deposition exhibit greater structural disorder in comparison to the highly ordered MAPI samples produced by other techniques such as mechanochemical grinding commonly used for NMR studies 35 .…”
Section: ) Results and Discussionmentioning
confidence: 98%
“…Comparative short-range structural and chemical information from 1D and 2D MAS NMR techniques will be sought from the as-synthesized and deposited MAPI substrates before and after exposure to electrical bias, to assess the resultant disordered systems induced by electrical stimulus. Previous studies have demonstrated that solid state MAS NMR is a powerful tool capable of resolving and identifying chemical species within the bulk and on the surface of hybrid perovskite systems, both in terms of direct chemical shift information and dynamics using relaxation measurements [31][32][33][34][35] . This non-destructive methodology is that it can quantitatively identify all species present irrespective of whether they are present within ordered or disordered structural environments.…”
Section: ) Introductionmentioning
confidence: 99%